Parents' and healthcare professionals' experiences of care after stillbirth in low‐ and middle‐income countries: a systematic review and meta‐summary. (17th September 2018) - Shakespeare, C; Merriel, A; Bakhbakhi, D; Baneszova, R; Barnard, K; Lynch, M; Storey, C; Blencowe, H; Boyle, F; Flenady, V; Gold, K; Horey, D; et al.
Abstract : Background: Stillbirth has a profound impact on women, families, and healthcare workers. The burden is highest in low‐ and middle‐income countries (LMICs). There is need for respectful and supportive care for women, partners, and families after bereavement. Objective: To perform a qualitative meta‐summary of parents' and healthcare professionals' experiences of care after stillbirth in LMICs. Search strategy: Search terms were formulated by identifying all synonyms, thesaurus terms, and variations for stillbirth. Databases searched were AMED, EMBASE, MEDLINE, PsychINFO, BNI, CINAHL. Selection criteria: Qualitative, quantitative, and mixed method studies that addressed parents' or healthcare professionals' experience of care after stillbirth in LMICs. Data collection and analysis: Studies were screened, and data extracted in duplicate. Data were analysed using the Sandelowski meta‐summary technique that calculates frequency and intensity effect sizes (FES/IES). Main results: In all, 118 full texts were screened, and 34 studies from 17 countries were included. FES range was 15–68%. Most studies had IES 1.5–4.5. Women experience a broad range of manifestations of grief following stillbirth, which may not be recognised by healthcare workers or in their communities. Lack of recognition exacerbates negative experiences of stigmatisation, blame, devaluation, and loss of social status. Adequately developed health systems, with trained and supported staff, are best equipped to provide the support and information that women want after stillbirth. Conclusions: Basic interventions could have an immediate impact on the experiences of women and their families after stillbirth. Examples include public education to reduce stigma, promoting the respectful maternity care agenda, and investigating stillbirth appropriately. Tweetable abstract: Reducing stigma, promoting respectful care and investigating stillbirth have a positive impact after stillbirth for women and families in LMICs. Tweetable abstract: Reducing stigma, promoting respectful care and investigating stillbirth have a positive impact after stillbirth for women and families in LMICs.